2009
DOI: 10.1302/0301-620x.91b1.21346
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, controlled trial of two mobile-bearing total ankle replacements

Abstract: We describe the results of a randomised, prospective study of 200 ankle replacements carried out between March 2000 and July 2003 at a single centre to compare the Buechel-Pappas (BP) and the Scandinavian Total Ankle Replacement (STAR) implant with a minimum follow-up of 36 months. The two prostheses were similar in design consisting of three components with a meniscal polyethylene bearing which was highly congruent on its planar tibial surface and on its curved talar surface. However, the designs were markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 12 publications
(9 reference statements)
2
98
0
3
Order By: Relevance
“…Bearing movement on the tibia indicates that the rolling element of the natural movement of the talus on the tibia [11,33,34] is reproduced. We found no mention of bearing movement in any of the reports of the current three-component devices with anatomic talar and flat tibial components [3,6,7,25,30,31,[50][51][52][53][54]. The overall AOFAS score improved by a mean of 40.5 points (38.5 preoperatively to 79.0 at 48 months) and was similar to the 45-point increase of the meta-analysis [48].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Bearing movement on the tibia indicates that the rolling element of the natural movement of the talus on the tibia [11,33,34] is reproduced. We found no mention of bearing movement in any of the reports of the current three-component devices with anatomic talar and flat tibial components [3,6,7,25,30,31,[50][51][52][53][54]. The overall AOFAS score improved by a mean of 40.5 points (38.5 preoperatively to 79.0 at 48 months) and was similar to the 45-point increase of the meta-analysis [48].…”
Section: Discussionsupporting
confidence: 57%
“…Our data with 51 ankles at risk during the first year and a 4-year survival rate of 97.2% suggest few postoperative complications requiring component removal in contrast to reports from the registries [15,24,26] or from experienced surgeons [3,6,7,25,30,40,42,[51][52][53] (Fig. 7).…”
Section: Aofas Scorementioning
confidence: 48%
See 1 more Smart Citation
“…Although studies have reported success rate of > 90% at 10 years using the STAR and Buechal Pappas (BP) implant [8], this data needs to be interpreted with caution as other studies using such implants are unable to reproduce similar success. Woods et al [9], an independent high volume unit, compared two different implants (STAR Vs BP) and reported only 79 % six year survivorship of the BP design as compared to 95% survivorship with the STAR design. This study had a relatively good sample of 200 patients, was a single centre study and was prospective in nature.…”
mentioning
confidence: 99%
“…1,2 Relatively poor clinical results have been described in patients with severe pre-operative angular deformity, [1][2][3][4][5] and higher rates of complication occur in congruent varus ankles. 2 Some authors have suggested that the indication for operation should be narrowed to those with < 10° to 15° of varus or valgus [1][2][3][4][5] and good results have been reported following arthrodesis of the ankle in patients with severe varus or valgus deformities of the ankle. 6 Between 33% 3 and 44% 2 of patients with endstage osteoarthritis present with malalignment of > 10° in the coronal plane.…”
mentioning
confidence: 99%